Digital Transformation of Fatwa Authorities: Comparative Analysis of MUI, Bahtsul Masail, and Muhammadiyah Tarjih - Nurbaeti; Muammar Bakry; Syatar, Abdul (MUI Sulawesi Selatan, 2025)
This study examines the transformation of the fatwa methodology of three major Islamic institutions in Indonesia, namely the Indonesian Ulema Council (MUI), Bahtsul Masā'il Nahdlatul Ulama (NU), and the Tarjih and Tajdid Council of Muhammadiyah in responding to digital transformation through the maqāṣid al-sharī'ah approach. This study uses a qualitative method based on a literature review of fatwas, institutional documents, and the latest academic literature on the epistemology of Islamic law in the digital era. The results of the analysis show that the three have different but complementary epistemological characteristics. The MUI presents an institutional maqāṣidī approach with a regulatory orientation, while NU maintains a model of ijtihād jamā'ī based on classical scientific traditions with a communitarian character. while Muhammadiyah develops an integrative rational framework through the bayānī, burhānī, 'irfānī model that is adaptive to developments in science and technology. In the context of digitalization, all three face the same challenge, namely maintaining scientific authority and the credibility of fatwas amid the proliferation of algorithms and religious content. However, this study emphasizes that the integration of maqāṣid al-sharī'ah values is key to balancing the authenticity of Islamic law and the demands of digital modernity. Therefore, the future direction of fatwa development should not only focus on the digitization of information systems, but also on the reconstruction of epistemological ijtihad towards a responsive digital maqāṣidī fiqh.